Bentuk Campur Kode dalam Video Pidato Wakil Presiden Gibran Rakabuming pada Kanal YouTube KOMPASTV - Husnu Amalia; Zaskiya Silfina Khafsah; Adrian Dually Ar Rasyid; Naufal Naufal; Rizka Rizka (Jurnal Kajian Ilmu Pendidikan, Bahasa dan Komunikasi, 2025)
This study aims to identify the forms of code-mixing present in the speech videos of Vice President Gibran Rakabuming, with the KOMPASTV YouTube channel serving as the data source. This phenomenon is interesting to examine because the use of code-mixing by state officials can influence public perceptions of the use of Indonesian in formal contexts, particularly in official speeches. The study employs a descriptive qualitative approach, using the observation and note method as the data collection technique. Data analysis was conducted through several stages, namely observing, noting, and then presenting as well as describing the forms of code-switching in Vice President Gibran Rakabuming’s speech videos. The results show that the type of code-mixing that occurs is outer code-mixing, characterized by the insertion of English vocabulary. The first video contained 9 instances of code-mixing, the second video 5 instances, the third video 4 instances, the fourth video 15 instances, and the fifth video 9 instances. These findings indicate that code-mixing is a phenomenon within the field of sociolinguistics and is commonly found among bilingual and multilingual communities.